The sons of Katie Elder [videorecording (DVD)] - Hathaway, Henry, 1898-1985; Jennings, Talbot; Wayne, John, 1907-1979; Martin, Dean, 1917-1995; Hyer, Martha (John Wayne Collection., 2007)
The day that Katie Elder is buried, her four sons return home to Clearwater, Texas, to pay their last respects. It is a he-man story, as well as, a drama of the maternal influence of Katie Elder, her sacrifice, love and incredible valor. The hopes and aspirations for her sons are movingly communicated from beginning to conclusion.